A generic interface for resource aggregation in grid of grids. (30th March 2011) - Surendran, D.; Purusothaman, T.; Balachandar, R.A.
This paper predicts some of the issues in the next generation grid infrastructure in which islands of grid will try to inter operate each other. The evolution of grid architecture and its related tools motivated many research organisations and institutes to deploy the grid in order to aggregate distributed computing resources to yield high performance computational power. However, these grids are not similar in their implementation as they use different middlewares. Looking ahead, when these grids need to inter operate with each other to form a grid of grids as well as for collaborative research activities between them, there comes a difficulty with respect to interoperability. In this paper, we highlight some of the issues related to interoperability such as aggregation of resource information and job submission across grid of grids. We propose an open, extensible generic interface for aggregating resource information across several middleware such as Globus, gLite and UNICORE. This component has been integrated with a semantic based resource discovery module that discovers suitable grid resources across different middleware based on their semantics. With the experimental analysis the performance of the proposed system is studied.